2016
DOI: 10.4236/oalib.1102836
|View full text |Cite
|
Sign up to set email alerts
|

Natural Water Conductivity Behavior within the Seismic Pacific Coast of Southern Mexico

Abstract: Near faults or unstable areas where an earthquake could happen with capacity to damage buildings or infrastructure, there is often a previous energy that wanders around surroundings, this energy regularly is associated with electromagnetic emissions that generate an electric potential frequently studied as very, ultra-low and extreme frequency emissions (VLF-ULF-ELF_ EM) by remote sensing; under the assumption that this natural potential exists, in aquatic environment within the micro-seismic active area in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The analysis of multiple 24-hour data series sets showed another pattern: the noticeable oscillations of natural conductivity between 7:00 to 22:00 hours, possibly related to human activity but, this influence is not very clear and proved truthfully, Figure 11 at [36]. The last one pattern observed revealed that during the total data monitoring of conductivity through 61 days there were three significant variations of natural conductivity in different periods (May 15 to 23; May 31 to June 9 and June 15 to July 9) highlighting the last period because showed that during the water conductivity increase run-up, there was null seismic activity but when water conductivity decreased, the seismic activity increased considerably with seismic events more of them with Mw < 4, Figure 13 at [36].…”
Section: Backgroundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of multiple 24-hour data series sets showed another pattern: the noticeable oscillations of natural conductivity between 7:00 to 22:00 hours, possibly related to human activity but, this influence is not very clear and proved truthfully, Figure 11 at [36]. The last one pattern observed revealed that during the total data monitoring of conductivity through 61 days there were three significant variations of natural conductivity in different periods (May 15 to 23; May 31 to June 9 and June 15 to July 9) highlighting the last period because showed that during the water conductivity increase run-up, there was null seismic activity but when water conductivity decreased, the seismic activity increased considerably with seismic events more of them with Mw < 4, Figure 13 at [36].…”
Section: Backgroundsmentioning
confidence: 99%
“…The second step of area analysis studied from March to July, 2016, emphasized the comparison of natural water conductivity data of two wells [36], both separated by 80 meters from each other, this focus showed other interesting patterns, one of them denoted the daily and frequent variation of natural conductivity possibly related to the internal flow of water, the groundwater movement is extremely fast indicating a vigorous groundwater recharge, possibly related to terrain compress or slight tilting of ground caused by very light earthquakes [10] [38] [39]. The analysis of multiple 24-hour data series sets showed another pattern: the noticeable oscillations of natural conductivity between 7:00 to 22:00 hours, possibly related to human activity but, this influence is not very clear and proved truthfully, Figure 11 at [36].…”
Section: Backgroundsmentioning
confidence: 99%